Comparison of the Effectiveness of Knowledge Conceptualization and Mindfulness Training on Students’ Self-Efficacy - Arabi, Meraj; Bigdeli, Hossein; Dabiri, Solmaz (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The purpose of this study was to compare the effectiveness of knowledge conceptualization training and mindfulness on students' self-efficacy. Methodology: The research method was quasi-experimental, utilizing a pre-test and post-test design with a control group. From the population of tenth-grade female students in public high schools in District 2 of Hamadan, 90 students were selected using single-stage cluster sampling and were randomly assigned to three groups of 30 (two experimental groups and one control group). The experimental groups received either knowledge conceptualization training (7 sessions) or mindfulness training (8 sessions), while the control group continued with their regular classroom activities. The General Self-Efficacy Questionnaire (Schwarzer & Jerusalem, 1982) was used to measure the dependent variable. Data were analyzed using one-way analysis of covariance (ANCOVA). Findings: The results indicated a significant difference in self-efficacy between the experimental groups (knowledge conceptualization and mindfulness) and the control group in the post-test stage after adjusting for pre-test scores. Moreover, knowledge conceptualization had a greater impact on students' self-efficacy compared to mindfulness training. Conclusion: Based on the results of the present study, it can be concluded that educational-psychological interventions, including knowledge conceptualization and mindfulness, can enhance students' adaptation to academic situations and facilitate the achievement of educational goals.